2021
DOI: 10.17942/sted.826753
|View full text |Cite
|
Sign up to set email alerts
|

Göğüs hastalıkları servisinde izlenmekte iken yoğun bakım ünitesine sevk edilen hastaların genel özelliklerinin irdelenmesi

Abstract: This study aimed to identify the overall characteristics of patients who were found as in need of intensive care while being monitored by chest diseases service in a training hospital. Material and Methodology: This study covered patients at Antalya Training and research Hospital who were referred from the chest diseases service to 3rd step intensive care in the period January-December 2017. The study covered all patients referred with the exception of those whose case files were yet incomplete. Findings: It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…Uzun et al reported the meropenem resistance to be 63.3% and piperacillin-tazobactam resistance to be 83.3%. (10). Although several studies have identified P. aeruginosa as one of the most common pathogens of the lower respiratory tract, this microorganism was detected in only 10 tracheal aspirate and 5 phlegm samples, which varied from the findings of relevant studies.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Uzun et al reported the meropenem resistance to be 63.3% and piperacillin-tazobactam resistance to be 83.3%. (10). Although several studies have identified P. aeruginosa as one of the most common pathogens of the lower respiratory tract, this microorganism was detected in only 10 tracheal aspirate and 5 phlegm samples, which varied from the findings of relevant studies.…”
Section: Discussionmentioning
confidence: 88%
“…As expected, the prevalence of lower respiratory tract infections was higher in the present study than in other studies as the present study was conducted in the respiratory ICU of the chest diseases department. A Turkish study conducted by Uzun et al reported that microbial growth was most frequent in the cultures of the respiratory tract samples (45.9%) in a respiratory ICU, followed by in those of blood samples (37.6%) (10)(11). Dundar et al elucidated that the culture samples taken in the ICU that showed the most frequent microorganism growth were obtained from the respiratory system (40%), blood-catheter (23%), urogenital system (15%), and skinsoft tissue samples (14%) (12).…”
Section: Discussionmentioning
confidence: 99%